The correlation between undergraduate student diversity and the representation of women of color faculty in engineering. Issue 4 (21st October 2020) - Main, Joyce B.; Tan, Li; Cox, Monica F.; McGee, Ebony O.; Katz, Andrew
Abstract: Background: Despite the critical role of faculty diversity in the persistence and academic experiences of undergraduate students as well as in the development of engineering innovations, women of color (WoC) faculty are still underrepresented in engineering programs across the United States. Purpose/Hypothesis: This study identifies whether the demographic composition of undergraduate engineering students is correlated with the representation of WoC faculty. It also highlights the institutional‐ and departmental‐level factors that contribute to the race–gender diversification of the engineering professoriate. Design/Method: Informed by organizational demography as the theoretical framework, the methods include linear and logit regression analyses. Data come from the American Society for Engineering Education, the Integrated Postsecondary Education Data System, and the American Community Survey, and include engineering departmental‐level observations across 345 institutions over 12 years. Results: Engineering departments that award more bachelor's degrees to women African American/Black undergraduate students are more likely to employ relatively more African American/Black women faculty. This positive relationship is also found among Asian Americans and Hispanics/Latinas. Conclusions: Research findings demonstrate the relationship between engineering undergraduate composition, as well as other departmental‐ and institutional‐level factors, and the prevalence of WoC faculty. The findings highlight important areas for stakeholders and academic administrators to consider when developing strategies and programs to diversify the composition of engineering faculty.